Home Garden Areas (KRPL) and Food Insecurity in Indonesia - Yudistira, Giskar; Susanti, Hera (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Food security is essential to ensure the availability, access, and consumption of sufficient, nutritious, and safe food for all people. The Home Garden Areas or Kawasan Rumah Pangan Lestari (KRPL) in the local language is one of the government's food security programs. The number of KRPLs has steadily increased between 2017 and 2021. However, the level of food insecurity has risen since 2020. Variations in the number of KRPLs from 2017 to 2021 were accounted for in this study to estimate their impact on food insecurity. This study recommends that KRPL be accompanied by other policies, particularly poverty reduction programs in food insecurity interventions, at least in regencies/municipalities with "high" and "very high" food insecurity categories. The magnitude and significance of the relationship between KRPLs and food insecurity were estimated using this study's panel data analysis techniques with the Fixed Effect method. According to the simulation results, an additional 157 KRPL areas are required in each regency and municipality to bring the SaMaPua regions into the "moderate" food insecurity category. The total number of KRPL needed for the SaMaPua region becomes 14.915 areas. The average food insecurity in Java-Bali from 2017 to 2021 is nearly half that of non-Javanese and Bali food insecurity. The maximum value of food insecurity in non-Java and Bali areas is 83,6 percent, indicating that there are still areas with "very high" food insecurity outside Java-Bali. According to the estimation results, KRPLs significantly reduce food insecurity after one year, particularly in the Java and Bali regions.